Female motorcyclists: psychosocial career and aspects of femininity - Χρηστάκης, Νικόλας; Αναλυτή, Αλεξάνδρα (The Greek Review of Social Research, 2013)
This paper explores the daily driving of motorcycles by women as a social phenomenon in its different variants. By analysing the life stories of twenty females thus constructing their career as motorcyclists, the study emphasises their experiential and timeless dimensions, while at the same time it focuses in the evolution of relationships in their familiar as well as their more extended environment. Moreover, in this paper it will be argued that the way in which these women «organise» and express their experiences and their thoughts concerning their motorcycling history, has everything to do with stereotype that motorcycling is a «male business». Having that in mind, it will be examined how they stage several, often very different, aspects of their feminine identities.